Burundi Gender Strategy: Building equitable climate resilient African bean and insect sectors - Hakizimana, Marie Bernadette; Ndabashinze, Blaise; Ouya, Frederick; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (Bioversity International and International Center for Tropical Agriculture, 2025)
The Building Equitable Climate-Resilient African Bean and Insect Sectors (BRAINS) project is driving sustainable change across 15 Sub-Saharan African (SSA) countries, including Burundi. The agricultural sector in Burundi remains the backbone of the rural population, enhancing food and nutrition security, household income, and job creation, with smallholder farmers depending mainly on rain-fed production systems (Nyamweru et al., 2024). However, the sector is increasingly subject to climate variability, including prolonged dry spells, irregular rainfall, pest and disease outbreaks, and weather-induced production shocks that affect production efficiency, market returns, and household resilience (Mperejekumana et al., 2023). These climate hazards overlap with longstanding socio-cultural and institutional inequities, including unequal access to land, financing, extension services, agro-weather information, and market opportunities, which disproportionately affect women, youth, people living with disabilities (PLWDs), and other marginalised farmers engaged across the value chains targeted by the project. Despite women’s significant contributions to agricultural labour, particularly in planting, harvesting, processing, and household food provision, they persistently face institutional barriers regarding resource access, decision-making power, and involvement in high-value market segments (Bamber et al., 2014). Men still maintain predominant control over land ownership, production choices, and revenue from commercial ventures, whilst youths encounter obstacles related to asset ownership, financial accessibility, and prospects for enterprise initiation (Niragira et al., 2011). These gendered inequalities limit the adoption of climate-smart innovations, diminish adaptive ability, and constrain equitable participation in developing market opportunities within the BRAINS project’s preferred common bean, fruit tree, and insect for food and feed value chains (Nchanji et al., 2023; Nchanji et al., 2024). The BRAINS project targets transforming the common bean, fruit tree, and insect for food and feed sectors by fostering low-carbon, climate-resilient systems and economies. The project is also committed to enhancing climate-resilient agricultural systems, promoting the adoption of climate-smart agriculture (CSA) technologies, and building a pipeline of enterprises actively investing in carbon-neutral, climate-resilient, socially inclusive agricultural systems and gender-responsive business development, in line with emerging goals of the climate finance sector. The Burundi Gender Strategy adopts the regional gender strategy through the broader Reach, Benefit, Empower, and Transform (RBET) framework, gender-transformative socio-technical innovation bundles (GTSTIBs), and inclusive value-chain development approaches adapted to the national context, also drawing from country-specific quantitative evidence